Awareness among Women on Allergy-inducing Foods in Infants and Young Children - Dziuba, Anna; Suwała, Grzegorz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The subject of this study was issues related to the food that causes allergies in infants and young children. The study gathered information on the awareness of mothers and future mothers on the risk of food allergies and knowledge of major products that cause allergies in infants and young children. A hundred correctly completed questionnaires were analysed, allowing the authors to determine the level of knowledge the women possessed on this subject. They also concluded that there was a range of ability, depending on the age of the respondents, to recognise early symptoms of allergy, the predisposition to inherit allergies and the duration of an allergy. There was no correlation between knowledge and the place of residence or the level of educational of either present or future mothers.